Composition and Diversity of Plant Seedlings and Saplings at Early Secondary Succession of Fallow Lands in Sabal, Sarawak - Karyati, -; Isa, Ipor; Ismail, Jusoh; Mohd Effendi, Wasli; Idris, Abu Seman (Universiti Putra Malaysia, 2013)
Seedlings and saplings represent the juvenile stage of plant life and their presence can reflect the future forests regeneration. However, still less information is available on the composition and diversity of seedlings and saplings under secondary forests at Sarawak, especially in fallow lands after shifting cultivation. In this study, the composition and diversity of plant seedlings and saplings in secondary forests at various age stands was conducted in order to obtain basic information on species under succession of secondary forests after shifting cultivation. A survey was carried out in four stages of fallows land such as 3 years.